Management of patients with cardiac implantable electronic devices (CIED) undergoing radiotherapy: A consensus document from Associazione Italiana Aritmologia e Cardiostimolazione (AIAC), Associazione Italiana Radioterapia Oncologica (AIRO), Associazione Italiana Fisica Medica (AIFM). (15th March 2018) - Zecchin, Massimo; Severgnini, Mara; Fiorentino, Alba; Malavasi, Vincenzo Livio; Menegotti, Loris; Alongi, Filippo; Catanzariti, Domenico; Jereczek-Fossa, Barbara Alicja; Stasi, Michele; Russi, Elvio; Boriani, Giuseppe
Abstract: The management of patients with a cardiac implanted electronic device (CIED) receiving radiotherapy (RT) is challenging and requires a structured multidisciplinary approach. A consensus document is presented as a result of a multidisciplinary working group involving cardiac electrophysiologists, radiation oncologists and physicists in order to stratify the risk of patients with CIED requiring RT and approaching RT sessions appropriately. When high radiation doses and beam energy higher than 6 MV are used, CIED malfunctions can occur during treatment. In our document, we reviewed the different types of RT and CIED behavior in the presence of ionizing radiations and electromagnetic interferences, from the cardiologist's, radiation oncologist's and medical physicist's point of view. We also reviewed in vitro and in vivo literature data and other national published guidelines on this issue so far. On the basis of literature data and consensus of experts, a detailed approach based on risk stratification and appropriate management of RT patients with CIEDs is suggested, with important implications for clinical practice.